2018
DOI: 10.1159/000491635
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Stroke Misdiagnosis in the Emergency Department: A Retrospective Case-Control Study

Abstract: Background: Failure to recognise acute stroke may result in worse outcomes due to missed opportunity for acute stroke therapies. Our study examines factors associated with stroke misdiagnosis in patients admitted to a large comprehensive stroke centre. Methods: Retrospective review comparing 156 consecutive stroke patients misdiagnosed in emergency department (ED) with 156 randomly selected stroke controls matched for age, gender, language spoken and stroke subtype for the period 2014–2016. Results: There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
3
27
0
Order By: Relevance
“…These results are consistent with the findings of a previous study, in which patients with stroke who had been misdiagnosed in the ED were more likely to be clinically assessed as negative for the face, arm, speech, and time (FAST) assessments. 20 The higher scores of the Cincinnati Prehospital Stroke Scale in the OAT 30 min group is consistent with the findings of a previous study, in which moderate to severe stroke symptoms are associated with the decision to choose EMS activation as the first medical attention for patients with acute stroke. 13 Among the factors related to EMS activation, onset occurrence at private space, wake-up strokes, recognition of symptoms from midnight to 8 am, unemployment, and witnessed by others were associated with delayed EMS activation.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the findings of a previous study, in which patients with stroke who had been misdiagnosed in the ED were more likely to be clinically assessed as negative for the face, arm, speech, and time (FAST) assessments. 20 The higher scores of the Cincinnati Prehospital Stroke Scale in the OAT 30 min group is consistent with the findings of a previous study, in which moderate to severe stroke symptoms are associated with the decision to choose EMS activation as the first medical attention for patients with acute stroke. 13 Among the factors related to EMS activation, onset occurrence at private space, wake-up strokes, recognition of symptoms from midnight to 8 am, unemployment, and witnessed by others were associated with delayed EMS activation.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion who had an ESS code indicating suspicion of a stroke/TIA or a neurological deficit was the same (3.4%). It has also been shown that, among patients who suffer from stroke and in whom the initial symptoms were vertigo, the risk of misdiagnosis is higher (Venkat et al, ) and about 30% of the cases were misinterpreted as having another disease (Saber Tehrani et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Doctors have reported a sudden decrease in the number of patients presenting to hospitals with acute neurological events such as stroke, likely due to fear of contracting COVID-19 infection (31,93,106). This is problematic as the delay in reperfusion therapy may have fatal consequences (107)(108)(109), especially to patients with underlying chronic neurological disease (30). Likewise, there are also concerns related to the postponement of elective surgeries, therefore, the impact of delayed surgery on long-term morbidity needs further study.…”
Section: Impact Of Covid-19 On Chronic Neurological Patientsmentioning
confidence: 99%